Performance Evaluation of Matching Gadgets for Camel Powered Rotary Transmission System - Bandyopadhyay, Archisman; Tiwari, G S; Mehta, A K (Annals of Arid Zone, 2016)
Camel is a major draught animal, which is widely used for agriculture and transportation purpose in arid and semi-arid regions of India. Still the major part of the animal power is unutilized. To enhance the utilization of draft animal power a rotary power transmission system is suitable method through which number of matching gadgets can easily be operated. A power transmission system was developed for the purpose. The system consisted of a set of crown, pinion and spur gears. The initial speed of rotation of animals was stepped up in the ratio of 1:125. A final drive shaft consisting of pulleys, fly wheel and a ratchet was provided to transmit power. The power was transmitted from gear box to this final drive shaft through an underground shaft encased in a pipe for operation of different matching gadgets. The system worked satisfactorily up to a draught of 125 kgf. Different matching machines namely maize dehusker sheller, groundnut decorticator and air compressor were operated by the power transmission system and their performance and animal’s fatigue level was evaluated. The draught requirement of the selected machines was well within the draught capacity of the animals. Key words: Draught animal power, rotary transmission system, load, matching gadgets, fatigue level, draught.